Covalently layer-by-layer assembled homogeneous nanolayers with switchable wettability. Issue 25 (2nd June 2015) - Topuz, Fuat; Möller, Martin; Groll, Jürgen
Abstract : A layer-by-layer growth through alternating chemisorption of isocyanate functional star-shaped polyethers (NCO-sP(EO-stat-PO)) and a linear polymer ((PVFA-co-PVAm)) is described. Abstract : Layer-by-layer (LbL) assembly is a practical and versatile approach to build up ultrathin hydrogel networks using mostly polyelectrolytes via alternate adsorption of oppositely charged molecules. It has recently been applied covalently by means of many different types of molecules, particularly those having low molecular weights or linear polymer structures. Using isocyanate (NCO) end-functional star-type polyethers (NCO-sP(EO- stat -PO)) in such covalent assemblies is a great challenge, since they are prone to form a smooth but non-reactive layer that precludes chemisorption of a subsequent layer. To overcome this problem, we developed a protocol where oligomers ( e.g., dimers, trimers) act as building blocks for a monolayer instead of single star shaped molecules. Since these are larger and multifunctional but still flexible, smooth layers thicker than a monomolecular film ( ca . 10 nm) result with sufficient mobility of the building blocks to bear enough reactive groups for covalent binding of a subsequent layer. As a second component for the chemical LbL layer buildup, a high molecular weight copolymer of vinylformamide/vinylamine (PVFA- co -PVAm) was used. The first layer was obtained by treating aminosilylated surfaces with NCO-s(EO- stat -PO) followed by incubation with PVFA- co -PVAm and chemical cross-linking with the first layer via urea links. The cycle was repeated to achieve the desired layer growth, and the resulting layers were characterized by ellipsometry, contact angle analysis, X-ray photoelectron spectroscopy (XPS), and scanning force microscopy (SFM). The amorphous structures of the polymers were revealed by WAXS analysis, suggesting the lack of the long-range order, which led to structural degree of freedom available to the polymer ( i.e., molecular flexibility) on the surface. Thus, multilayers were obtained with homogeneous structure together with low roughness values, and the water contact angles of the layers switched between 37 and 45° depending on the terminal layer. The layers were stable over three months under humid conditions during which no significant changes could be observed in thickness and hydrophilicity.